Mapping the Geographic Distribution of Large Branchiopods in Algeria and a checklist update - Chergui, Isslam; Satour, Abdellatif; Bouzid, Abdelhakim; Koulali, Khaled; Samraoui, Boudjéma (Zootaxa, 2023)
The objective of this study was to assess the diversity and distribution of large branchiopods in the Algerian Sahara and Hauts Plateaux. The survey identified a total of eleven species, classified into seven Anostraca, two Notostraca, and two Spinicaudata. Large branchiopods were found in 76.6% of the sites surveyed. In particular, new records of Triops granarius (Lucas, 1864) were obtained from the Tasilli N’Ajjer region (Central Sahara), while Eocyzicus saharicus (Gauthier, 1937) was added to the list of large branchiopods of Algeria, bringing the total number of species in Algeria to twenty-four. In addition, this study examines the latitudinal gradient of major branchiopod assemblages in Algeria, extending from the northern Mediterranean coast to the arid regions of the Sahara. The study identifies eight major assemblages of large branchiopods distributed across different ecoclimatic zones that occur along the latitudinal and longitudinal axes of the country. In addition, the study draws parallels between Algerian assemblages and those in neighboring Morocco and Tunisia.